The Effects of Questioning Skills Training on Question Forming Levels of Turkish Secondary School Students - Selim Bülbül; Serdar Derman (Ana Dili Eğitimi Dergisi)
This study was conducted to determine the effect of question-asking skills training on the distribution of students' generated questions according to the stages of the reading process and the cognitive process dimension of the revised Bloom's taxonomy. The research employed a quasi-experimental design with a pre-test and post-test control group. The sample consisted of 58 fifth-grade students during the 2016–2017 academic year. The data were collected through a narrative text administered to both groups. During the research process, the experimental group received 16 hours of training on question-asking skills. The collected data were analyzed using content analysis. Subsequently, the Wilcoxon Signed-Rank Test was used to identify changes in the cognitive process dimension of the revised Bloom’s taxonomy. The findings revealed that, in the pre-test, both groups benefited from questions only after reading and mostly generated questions at the lower-order thinking levels of remembering and understanding. In the post-test, the questions generated by the control group were similar to those from the pre-test. However, the experimental group produced questions covering all stages of the reading process. Additionally, in the post-test results, a significant difference was found in the distribution of the questions generated by the experimental group across the cognitive process dimension—except for the remembering and applying levels. The experimental group also generated questions at the evaluating and creating levels. The findings demonstrate that question-asking skills training enables students to utilize questions more effectively throughout the reading process.